2004
DOI: 10.1111/j.1747-7379.2004.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Ethnic Entrepreneurship: Convergencies, Controversies, and Conceptual Advancements

Abstract: In the past thirty years, many concepts and theories on ethnic entrepreneurship have been developed, challenged, and revised to provide a fuller account of the phenomenon. This article revisits the existing literature to address some of the conceptual and methodological issues and the controversies that have lingered around them and to highlight important advancements that have broken through conventional frameworks of this lasting subject matter. It first reexamines the meaning and analytical distinction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
543
1
146

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(703 citation statements)
references
References 60 publications
13
543
1
146
Order By: Relevance
“…At the societal level structural barriers can prevent particular groups of immigrants and ethnic minorities from competing with the native born on an equal basis in the mainstream economy (Zhou 2004). As a consequence, some immigrants and minorities can be pushed into self-employment to a larger extent than others.…”
Section: Theories On Immigrant Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…At the societal level structural barriers can prevent particular groups of immigrants and ethnic minorities from competing with the native born on an equal basis in the mainstream economy (Zhou 2004). As a consequence, some immigrants and minorities can be pushed into self-employment to a larger extent than others.…”
Section: Theories On Immigrant Entrepreneurshipmentioning
confidence: 99%
“…At the group level, the phenomenon of immigrant entrepreneurship is associated with group-specific cultural values, behavioural patterns, distinct group traits, social structures, collective resources and coping strategies (Zhou 2004). Light's cultural theory (1972) states that some groups of immigrants are more predisposed to entrepreneurship than others due to their sociocultural background.…”
Section: Theories On Immigrant Entrepreneurshipmentioning
confidence: 99%
“…As mentioned already, the mainstream literature on 'ethnic 1 3 entrepreneurship' increasingly focuses on the transnational economic activities of so-called ethnic or migrant entrepreneurs, thereby assuming that every entrepreneur is automatically transnationally active, possessing 'transnational capital' (Rusinovic 2008;Ambrossini 2012;Portes et al 2002;Zhou 2004). Our interviews have, however, shown that transnational economic activities, transnational capital, or transnational links do not play a significant role in the economic activities of female entrepreneurs.…”
Section: Gendering Mobility Capital and Transnational Capitalmentioning
confidence: 79%
“…The pluri-local, transnational, interactive relationships of migrants and their descendants were and are largely ignored and not systematically explored (Portes et al 2002, p. 284;Goebel and Pries 2006, p. 264) due to the fact 1 3 that methodological nationalism (Wimmer and Glick Schiller 2003) has been and still is prevalent. Due to this focus, it has long been overlooked that many migrant businesses depend on regular contact with their countries of origin or, as for example Zhou (2004) argues, on social networks across space. Neither has it been discussed that so-called local 'ethnic' economies are increasingly part of global production (Portes et al 2002).…”
Section: Who Is a Migrant Or 'Ethnic' Entrepreneur?mentioning
confidence: 99%
“…Bonacich and Modell, 1980;Portes and Bach, 1985;Borjas, 1986;Waldinger, 1990). Zhou argues that 'immigrants seek self-employment in greater proportion than natives do because of discrimination in the larger labor market and disadvantages associated with immigrant status, such as poor English proficiency and the depreciation of human capital' (Zhou, 2004(Zhou, , p. 1047. Whereas, culture and ethnic economy or 'the ethnic resource model' (Ram and Jones, 2008) have been the dominant hypotheses in the US literature, the 'breadwinning hypothesis' has had a larger impact in European research (Kloosterman, 2010;Clark and Drinkwater 2000).…”
Section: Theorymentioning
confidence: 99%